Phase 1 Cardiac Rehabilitation in Acute Coronary Syndrome Patients: A Literature Review - Reza Ariyanur; Aan Nuraeni; Anastasia Anna; Marlynda Triana; Nehemia Simanjuntak; Neli Hartini; Oktavia Nu razizah Jain; Plita Muliahati; Rahmah Tresnala; Rian Nugraha; Rizki Mardhotulloh Syarief; Rizkiani Tri Ramdani; Rosi Handayani; Septi Rizki Amaliyah; Shasqia Novelia Dingri; Sheren Yolavia (Padjadjaran Acute Care Nursing Journal, 2021)
The provision of phase I cardiac rehabilitation intervention in patients with cardiovascular disease needs to be given because it can accelerate recovery and determine the needs of the next phase of cardiac rehabilitation, namely phases II, III and IV.  The aim of this study was to find out the impact of phase 1 cardiac rehabilitation on acute coronary syndrome patients. This literature study examined scientific articles published from 2011 to 2021 and in Indonesian and English. Data was obtained from the database includes PubMed, Cinahl Ebscohost and Google Scholar search engine using keywords developed based on population, concept and context namely Cardiac Patients, Phase 1 of Cardiac Rehabilitation, Outcomes, Benefits and Effects. A total of 275,000 articles were obtained and after being selected based on duplication, title, abstract and inclusion criteria were obtained 9 articles that are eligible for analysis. The results of the study found that phase 1 cardiac rehabilitation in SKA patients was shown to have good impact and outcomes, such as improving quality of life and self-efficacy, reducing the need for the second phase of rehabilitation, and reducing the level of anxiety and depression experienced by SKA patients. Therefore, the results of this literature review can be the basis of the next research in the implementation of phase 1 cardiac rehabilitation in Indonesia.